Research on the Influence and Countermeasures of China’s Intellectual Property Rights on the New Energy Vehicle Industry - Yu Yahui (SHS Web of Conferences)
The enhancement of environmental awareness and the advancement of energy structure adjustments are driving forces behind achieving carbon peak and carbon neutrality. These efforts have also spurred the innovative development of future energy industries, including hydrogen and electric energy. Within this context, the growth of new energy vehicles, such as clean energy vehicles, has garnered significant attention in China. Patents, as a key indicator of a company’s innovation capability and market competitiveness, are crucial in evaluating the progress of the automotive industry. To better understand the development trajectory of China’s leading automobile companies, this article selects several prominent domestic manufacturers as the focus of its analysis. By examining the current status and historical development of these companies, alongside an in-depth analysis of their patent portfolios—considering factors such as competitiveness, volume, and technological impact—this study aims to provide a comprehensive overview of their innovation landscape. Based on these insights, the article offers three strategic recommendations: First, it is essential to enhance the quality of patents, ensuring they are not only numerous but also impactful. Second, companies should intensify research and development efforts in critical areas, targeting breakthroughs in key technologies. Third, proactive patent layouts for forward-looking and emerging technologies should be pursued to secure long-term competitive advantages.